The Role of the Bidding Process in Price Determination : Jump Bidding in Sequential English Auctions - Yaron Raviv (Claremont McKenna College, Department of Economics, 2004)
I study the sequence of bidding in an open-outcry English auction to examine how the strategic bidding process affects price determination. I do this by studying the anomalous nature of "jump bidding" in data I have collected from a series of public auctions of used cars in New Jersey. Jump bidding occur when a new offer is submitted that is above the old offer plus the minimum bid increment permitted. I find that jump biddings are an empirical regularity in all items sold. The jumps are a function of the presale estimate of the item?s price but are not affected by the selling order. I suggest a way to use the Jump Biddings to determine whether an open-outcry auction is best interpreted with models that assume private-or common-item valuations, and conclude that these auctions are consistent with the common values interpretation.
Keywords: D44; 330; Auction; Auktionstheorie; Marktmechanismus